Composition of soil fungi in oil palm plantation, Sungai Asap, Sarawak. - Wong, Sharon; Wong, Sing King; Ahmad, Khamirulmazmi; Ahmad Ali, Siti Ramlah (2012)
Oil palm industry in MAlaysia is expanding rapidly due to high demand from cooking oil and biofuel markets worldwide. The oil palm plantation activities may lead to biodiversity loss to certain extent. A study was carried out to compare the composition of soil fungi in oil palm plantation and the adjacent secondary forest in Sungai Asap, Sarawak using denaturing gradient gel electrophoresis (DGGE). Amplification of fungal 185 rDNA was achieved with universal primers. A total of 122.77 and 95 fungi were recorded from two forest soils and a plantation soil. Sequence analysis and cluster analysis pf prominent DGGE bands showed that the fungal community in plantation was different from those in the forests. Two main ohyla were observed namely Ascomycota and Basidiomycota. Forest soils consist of 67.9% and 53% of Basidiomycota whereas 30.3% and 47% were Ascomycota. In contrast, 12.8% Basidiomycota and 87.2%. Ascomycota were found in plantation soil. From the resresentative bands, sequences showed 1 fungus were common between two forest sites, 5 funsi species were common between secondary forest and plantation soil yet no common species were found among the three study sites. Some groups of the soil fungi could be potentially used as indicator to access soil quality at oil plam plantation.